Efecto inhibitorio in vitro de tres pastas de obturación para pulpectomia sobre enterococcus faecalis atcc 29212 y staphylococcus aureus. ATCC 65358 - Castillo Blaz, Sally Esperanza (2014)
This study aimed to determine the in vitro inhibitory effect of three pastas shutter pulpectomy on the growth of ATCC 29212 and Enterococcus feacalis Staphylococcus aureus ATCC 65358 were evaluated Pasta MCM ( metronidazole , ciprofloxacin and minocycline ) , MCMP ( metronidazole , ciprofloxacin minocycline , prednisone ) , and taking Vitapex vancomycin Gold standard for microorganisms. The prospective , longitudinal and experimental study ; included a total of 60 petri plates containing specific microorganisms within their respective culture medium ; following the criteria of inclusion and exclusion, of which 54 petri plates could be evaluated. As regards the comparison of the inhibitory effect of pasta to pulpectomy on growth of enterococcus bacteria feacalis , when performing the simultaneous compared using the t test analysis of variance equal average effects are rejected, indicating that at least one of the pastas have different average effect , with a highly statistically significant difference ( p < 0.01). Using the Duncan test as post- ANOVA test is done to complement the peer analysis evidenced significant differences between VS Vitapex MCM , MCM VANCOMYCIN VS , VS Vitapex MCMP , MCMP VANCOMYCIN VS and VS Vitapex VANCOMYCIN